Combating Corruption legal approaches to supporting good governance and integrity - Hatchard, John. (Cheltenham Edward Elgar, 2014)
Drawing on numerous recent examples of good and bad practice from around the continent, this insightful volume explores the legal issues involved in developing and enhancing good governance and accountability within African states, as well as addressing the need for other states worldwide to demonstrate the 'transnational political will' to support these efforts. John Hatchard considers the need for good governance, accountability and integrity in both the public and private sector. He studies how these issues are reflected in both the African Union Convention on Preventing and Combating Corruption and the United Nations Convention Against Corruption. The book demonstrates that despite the vast majority of African states being party to these conventions, in practice, many of them continue to experience problems of bad governance, corporate bribery and the looting of state assets. It explores how the 'art of persuasion' can help develop the necessary political will through which to address these challenges at both the national and transnational levels. This unique and influential book will be of worldwide interest to those studying law, politics or business, as well as legal practitioners, policymakers, senior public officials, parliamentarians, law reformers, civil society organizations and the corporate sector.
Includes index
Keywords: Corruption